Soil phytolith assemblages reflect palm community composition in western Amazonia - McMichael, Crystal N.H.; Guerra, Daniel; Witteveen, Nina H.; Heijink, Britte M.; Zwarts, Annabel; Zuquim, Gabriela; Balslev, Henrik; Ruokolainen, Kalle; Tuomisto, Hanna (Elsevier BV, 2026)
Humans have domesticated and used palms in tropical forests for millennia. The extent to which past human palm use affects modern tropical systems remains relatively unexplored due to lack of a good fossil record. However, palms produce an array of phytoliths, which are siliceous cell structures that preserve well in the soil even after the organic plant material has decayed. Phytoliths vary in morphology and can be identified to group level and sometimes even to species. We analyzed if palm phytolith assemblages sampled from the soil reflect palm species compositions and abundances in 63 western Amazonian transects. Principal coordinate analysis (PCoA) and Mantel tests showed that palm communities and phytolith assemblages had similar turnover patterns. Negative binomial generalized linear models indicated that the abundances of nine of the 13 common palm genera were significantly related to a combination of soil cation concentrations, grass phytolith percentages, and palm phytolith PCoA axis scores. These results suggest that phytoliths have potential as quantitative indicators of changes in palm abundances in paleoecological and archaeological reconstructions.